2021
DOI: 10.1113/ep089461
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the vascular response to sympathetic activation during acute hypoxaemia

Abstract: Activation of the sympathetic nervous system causes vasoconstriction and a reduction in peripheral blood flow. Sympathetically mediated vasoconstriction may be attenuated during systemic hypoxia to maintain oxygen delivery; however, in predominantly male participants sympathetically mediated vasoconstriction is preserved or even enhanced during hypoxaemia. Given the potential for sex-specific differences in hypoxic vascular control, prior results are limited in application. We tested the hypothesis that young … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 68 publications
1
8
0
Order By: Relevance
“…In fact, there is compelling evidence of an upregulated β‐adrenergic responsiveness of the peripheral vasculature to sympathetic outflow in premenopausal women (Hart et al., 2011; Kneale et al., 2000) and, as such, the vasodilatory response to hypoxic exercise is higher in women compared to men (Casey et al., 2014). Moreover, Jacob and colleagues (2021) recently reported that acute hypoxia increases the vasoconstrictor response to other sympathoexcitatory stressors (e.g. cold pressor test) in men, but attenuates the response in women, a finding which further substantiates the current conclusion of the sex difference in the MMR:O 2 ‐CR interaction.…”
Section: Discussionsupporting
confidence: 79%
“…In fact, there is compelling evidence of an upregulated β‐adrenergic responsiveness of the peripheral vasculature to sympathetic outflow in premenopausal women (Hart et al., 2011; Kneale et al., 2000) and, as such, the vasodilatory response to hypoxic exercise is higher in women compared to men (Casey et al., 2014). Moreover, Jacob and colleagues (2021) recently reported that acute hypoxia increases the vasoconstrictor response to other sympathoexcitatory stressors (e.g. cold pressor test) in men, but attenuates the response in women, a finding which further substantiates the current conclusion of the sex difference in the MMR:O 2 ‐CR interaction.…”
Section: Discussionsupporting
confidence: 79%
“…As a result, males may have greater vasodilatory reserve when faced with a potent local vasodilatory stimulus (i.e., local tissue hypoxia, explaining the twofold increase in vascular conductance when exposed to hypoxia we observed in males compared females ( than females, despite matched microvascular function (Kobayashi et al, 2015). Additionally, the forearm vascular response to hypoxia has been observed to be greater in males (Jacob et al, 2021), but this is not a finding shared by all studies (Casey et al, 2014).…”
Section: Isolated Effect Of Acute Hypoxiamentioning
confidence: 63%
“…This latter study was the first to directly compare hemodynamic stress responses in head muscles and included an extensive review of the recent literature, although head muscles were limited to the masseter muscle (Rashid and Roatta 2022 ). Limb muscles were no longer examined in the present study but sympathetic constrictory responses or increases in muscle sympathetic nerve activity in these muscles have consistently been reported in response to several stressors, including cold pressor test (Wray et al 2007 ; Jacob et al 2021 ; Coovadia et al 2022 ), post-exercise muscle ischemia (Saito et al 2000 ; Tokizawa et al 2006 ), and acute pain stimuli (Burton et al 2016 ).…”
Section: Discussionmentioning
confidence: 95%